#TITLE_ALTERNATIVE# - Hariyanto (NIM S2 828405), Teguh
Abstract: The detection of concrete beams deflection is one of civil engineering work, for knowing the strong of concrete beam caused by the difference load. To get the deflection-value directly is used a dialtest, in which a dial instrument is placed in a certain place. This research investigated the possibilities of the use photogrammetry method by using non-metric camera to detect the deflection which occurs in many points places of the concrete beam. The result we can get are x and y directions in many concrete beams points with the accuracy of 0.731 mm and 0.741 mm. The deflection value ( y derection ) has not been used to substitute the deflection value which can get directly. The deflections direction which is the resultant of x and y directions can be used one of the input to analyse materials caused by difference load.